Spin dictators: The changing pace of tyranny in the 21st century - Guriev, Sergei; Trisman, daniel (New Jersey Princeton university press, 2022)
How a new breed of dictators holds power by manipulating information and faking democracy Hitler, Stalin, and Mao ruled through violence, fear, and ideology. But in recent decades a new breed of media-savvy strongmen has been redesigning authoritarian rule for a more sophisticated, globally connected world.
Keywords: Spin doctors; Liberal democracy; Dictatorship